2010
DOI: 10.1111/j.1600-0412.2010.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical insulin‐like growth factor binding protein‐1 (IGFBP‐1) to predict spontaneous onset of labor and induction to delivery interval in post‐term pregnancy

Abstract: IGFBP-1 predicts both spontaneous labor onset and successful induction in post-term pregnancy. Bishop score and cervical length performed equally well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 17 publications
3
13
1
2
Order By: Relevance
“…considered that cervical phIGFBP‐1 predicted both spontaneous labor onset and successful induction in post‐term pregnancy . In agreement with previous studies we showed that in women with a negative dipstick test the concentrations of IGFBP‐1 and phIGFBP‐1 were higher in term than in preterm pregnancies . In dipstick‐test‐negative women the cervical status did not affect IGFBP‐1 concentrations, regardless of the presence of blood.…”
Section: Discussionsupporting
confidence: 91%
“…considered that cervical phIGFBP‐1 predicted both spontaneous labor onset and successful induction in post‐term pregnancy . In agreement with previous studies we showed that in women with a negative dipstick test the concentrations of IGFBP‐1 and phIGFBP‐1 were higher in term than in preterm pregnancies . In dipstick‐test‐negative women the cervical status did not affect IGFBP‐1 concentrations, regardless of the presence of blood.…”
Section: Discussionsupporting
confidence: 91%
“…We performed a PubMed search on 7 January 2016 using the search terms ‘insulin growth factor binding protein 1’ OR ‘IGFBP‐1’ AND ‘labor induction’ OR ‘labour induction’, without any limits, which returned 12 articles: only four of these papers that we further discuss below are original reports presenting primary data on IGFBP‐1 as a predictor of inducibility of labour in women with intact membranes …”
Section: Discussionmentioning
confidence: 99%
“…In a secondary analysis of a randomised controlled trial on prolonged pregnancy in a heterogeneous population of nulliparous and parous women, IGFBP‐1 predicts both spontaneous labor onset and successful induction. Bishop score and cervical length perform equally well …”
Section: Introductionmentioning
confidence: 89%
“…Cependant, il est important de noter que toutes les études ayant étudié les facteurs de risque de césarienne après déclenchement du travail chez les patientes ayant une grossesse prolongée [52][53][54][55][56] …”
Section: Influence De La Paritéunclassified
“…Cependant, la longueur cervicale mesurée par échographie endovaginale ne semble pas avoir une meilleure prédictivité que le score de Bishop pour le taux d'accouchement par les voies naturelles après déclenchement pour grossesse prolongée [53,54] (NP4). L'échographie 3D du col utérin (volume utérin et Doppler 3D) ne semble pas corrélée au taux d'accouchement par les voies naturelles après déclenchement pour grossesse prolongée [54] (NP4).…”
Section: Déclenchement (N = 254)unclassified